Promoting Autonomous Learning in Reading Class - Sholeh, Agus (JEELS (Journal of English Education and Linguistics Studies), 2015)
To have good acquisition and awareness in reading, the learners need a long and continuous process, and therefore, they are required to have autonomy in learning reading. This study aims to promote learner autonomy in reading class by combining learner-centered reading teaching and extensive reading teaching. Learner-centered reading teaching was carried out through group discussion, presentation, and language awareness activities. Meanwhile, extensive reading teaching was done to review the learners‘ materials in presentation and reinforce their acquisition. Those two different approaches were applied due to differences on learner's characteristics and needs. The result showed some success in the practice of autonomy, indicated by changes on learners' attitude. However, many learners showed that they focused more on obtaining score than on developing their language acquisition. By implementing the approach, the teacher can assist learners to be aware of their ability to learn independently and equip them with the skill needed for long-life learning.